Sara and the search for normal - King, Wesley (Simon & Schuster Books for Young Readers, 2020)
Seventh-grader Sara just wants to be normal, but instead she deals with panic attacks and other issues that make her avoid other people. When she starts group therapy, she meets talkative and outgoing Erin, who doesn't believe in "normal." Sara soon finds herself with an actual friend, but discovers that there's more to Erin than she lets on. In order to help Erin, Sara might have to sacrifice their friendship.